Asymmetric Ketone Reduction by Imine Reductases. (30th December 2016) - Lenz, Maike; Meisner, Jan; Quertinmont, Leann; Lutz, Stefan; Kästner, Johannes; Nestl, Bettina M.
Abstract: The rapidly growing area of asymmetric imine reduction by imine reductases (IREDs) has provided alternative routes to chiral amines. Here we report the expansion of the reaction scope of IREDs by showing the stereoselective reduction of 2, 2, 2‐trifluoroacetophenone. Assisted by an in silico analysis of energy barriers, we evaluated asymmetric hydrogenations of carbonyls and imines while considering the influence of substrate reactivity on the chemoselectivity of this novel class of reductases. We report the asymmetric reduction of C=N as well as C=O bonds catalysed by members of the IRED enzyme family. Abstract : IRED vs. KRED : Asymmetric reduction of a highly reactive carbonyl compound has been accomplished with an imine reductase. Kinetics and in silico studies have yielded mechanistic insights, thus allowing an understanding of this promiscuous behaviour.